Functional analysis of a novel homozygous missense IVD gene variant: a case report with dual genetic diagnoses - Yuying Zhu; Ke Wu; Hanying Wen (Frontiers in Pediatrics)
BackgroundGenomic or exome sequencing is beneficial for identifying more than one pathogenic variation causing blended atypical and/or severe phenotypes. Herein, we are the first to report a 5-year-old boy with the blended phenotypes of infantile hypotonia, severe neurodevelopmental disorder, patent ductus arteriosus, cryptorchidism, obesity, distinctive facial features, and elevated isovaleryl carnitine.MethodsTrio-based whole-exome sequencing was performed on genomic DNA from peripheral blood samples from the boy and his parents. Functional analysis of the IVD variant in vitro was performed. Mutant IVD gene pcDNA3.1(+)-MUT-3xFlag and control pcDNA3.1(+)-WT-3xFlag mammalian expression vectors were constructed. Both vectors were transformed into HEK293T cells. The assays of relative IVD gene mRNA expression, IVD protein expression, and enzymatic activity were used.ResultsWhole-exome sequencing identified a novel homozygous missense variant in the IVD gene (NM_002225.5) c.1006T>C (p.Cys336Arg) within a region of homozygosity of 15q11.2-q21.3. Our in vitro functional and computer simulation findings revealed that this variant was associated with haploinsufficiency, which resulted in dramatically reducing the formation of IVD protein due to unstable mutant protein and not a lack of mRNA expression.ConclusionThe boy was diagnosed with the dual genetic disorders of Prader–Willi syndrome and isovaleric acidemia. This case provides a useful reference for genetic counseling for complex and diverse clinical phenotypes. The presence of two or more likely pathogenic or pathogenic variations in an individual with neurodevelopmental phenotypes is not an “exceptional” phenomenon.